2007
DOI: 10.1007/s00024-007-0250-3
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Offsets in the Moho: Synthetic Tests using Gaussian Beams with Teleseismic Waves

Abstract: We carry out a sequence of numerical tests to understand conditions under which rapid changes in crustal thickness can be reliably imaged by teleseismic body waves. Using the finite-difference method over a 2-D grid, we compute synthetic seismograms resulting from a planar P-wavefield incident below the grid. We then image the Moho using a migration scheme based on the Gaussian beam representation of the wavefield. The use of Gaussian beams for the downward propagation of the wavefield is particularly advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Vertical and radial component ray/Born synthetics have been generated and are shown in Figure 3, where the scattering is incorporated by using point scatterers within a background two-layer model similar to that used by Shragge et al (2001) for their test migrations. More complete finite-difference simulations have been performed by Nowack et al (2004), and similar inversion results were found for the Gaussian beam imaging. The source is a plane P-wave incident from beneath the structure at a 20Њ angle from the vertical with a Gaussian pulse width of 1 sec.…”
Section: Applications Of Gaussian Beam Migrationsupporting
confidence: 55%
“…Vertical and radial component ray/Born synthetics have been generated and are shown in Figure 3, where the scattering is incorporated by using point scatterers within a background two-layer model similar to that used by Shragge et al (2001) for their test migrations. More complete finite-difference simulations have been performed by Nowack et al (2004), and similar inversion results were found for the Gaussian beam imaging. The source is a plane P-wave incident from beneath the structure at a 20Њ angle from the vertical with a Gaussian pulse width of 1 sec.…”
Section: Applications Of Gaussian Beam Migrationsupporting
confidence: 55%
“…We have chosen the GB approach to calculate the wave fields (Nowack et al, 2006(Nowack et al, , 2007; Appendix A) for the migration and imaging of teleseismic P-S conversions, and this choice distinguishes our method from alternatives such as those of Bostock and Rondenay (1999) and Bostock et al (2001), whose algorithms are based on geometric rays. A key advantage of the GB approach is its ability to handle triplicate (caustic) arrivals in the wave field without any special treatment.…”
Section: Imaging Of Teleseismic P-wave Data Using Gaussian-beam Migramentioning
confidence: 99%
“…This approach assumes one-dimensional (1D) structures for all calculations to construct two-dimensional (2D) images and then typically applies some arbitrary scheme to smooth the resulting product by averaging values from neighboring cells (bin averaging). In contrast to recent developments in imaging techniques (Bostock et al, 2001;Nowack et al, 2006Nowack et al, , 2007, the CPP approach utilizes only a fraction of the information in the scattered wave field. The difference in methodology distinguishes the current study from other recent work (Hetényi et al, 2007).…”
Section: Imaging Of Teleseismic P-wave Data Using Gaussian-beam Migramentioning
confidence: 99%
See 1 more Smart Citation
“…Other solutions emphasize the analysis of reflected waves, especially from artificial sources of seismic waves, and such measurements provide some of the most important information for applications such as hydrocarbon exploration [Beylkin (1985); Bleistein et al (2001); de Hoop and Bleistein (1997); Lambaré (2003)]. Recent research has also been extending the application of such methods to apply them to seismic waves generated by natural sources to image the structure of earth's crust and mantle [Bostock and Rondenay (1999); Nowack et al (2007); Wittlinger et al (2004)]. …”
Section: Introductionmentioning
confidence: 98%